Corporate Criminal Liability and Abolitionism – An unholy alliance of corporate power and critical criminology? - Anne Alvesalo-Kuusi; Steven Bittle; Liisa Lähteenmäki (EG Press, 2022)
Abolitionists have, since the 1960s, importantly denounced incarceration as ineffective, notably in terms of deterrence. It is thought to increase human suffering. Abolitionists reject the concept of crime, dismiss punitive responses to social problems and propose that they should be dealt with outside the criminal justice system. Nevertheless, these calls for social justice are time and again declared by the establishment to be unfeasible, romantic illusions.  Yet, this article demonstrates that, when it comes to regulating the harmful acts of corporations, certain classic abolitionist arguments are taken seriously and conveniently co-opted by the establishment. Using unparalleled data concerning both law-making history and recent corporate fine sentences in Finland, we scrutinise the enactment and implementation of corporate criminal liability, and establish how select abolitionist arguments, often deemed impossible and demoralising in the context of individual offences, triumph when corporate interests are at stake.